Speaker, leader, champion : succeed at work through the power of public speaking - Donovan, Jeremey; Avery, Ryan (McGraw Hill-Ascent Audio, 2014)
The secrets of superb public speaking-based on the best of the best of Toastmasters Toastmasters, a name synonymous with public speaking, is dedicated to developing its members' communication and leadership skills. Now Distinguished Toastmaster Jeremey Donovan and Public Speaking World Champion Ryan Avery break down the winning speeches from Toastmasters' prestigious annual competition-providing you with tips and techniques guaranteed to improve your speaking, presentation, and communication skills. They also include a special section of insights and advice for readers who aspire to become serious public speaking competitors. "Speaker, Leader, Champion demystifies what makes a presentation extraordinary. This engaging, actionable book will teach you how to go from appreciating a powerful speech to delivering one yourself."--Adam Grant, professor at the Wharton School at the University of Pennsylvania and New York Times bestselling author of Give and Take "Whether you present in the boardroom, classroom, or lunchroom, the guidance will help you become a more confident, authentic, and engaging speaker." -Matt Abrahams, strategic communication lecturer at the Stanford University Graduate School of Business and author of Speaking Up Without Freaking Out "To change the world, you need to lead. To lead, you need to communicate. To communicate, you need this book." -Presiyan Vasilev, 2013 World Champion of Public Speaking "This book translates the secret sauce of public speaking into easy-to-use tips." -Zoe Chance, assistant professor of marketing at the Yale University School of Management